The calcium connection: exploring the intricacies of calcium signaling in plant-microbe interactions - Negi, Neelam Prabha; Prakash, Geeta; Narwal, Parul; Panwar, Ruby; Kumar, Deepak; Chaudhry, Bharti; Rustagi, Anjana (Frontiers in Plant Science, 2023)
The process of plant immune response is orchestrated by intracellular signalling molecules. Since plants are devoid of a humoral system, they develop extensive mechanism of pathogen recognition, signal perception, and intricate cell signalling for their protection from biotic and abiotic stresses. The pathogenic attack induces calcium ion accumulation in the plant cells, resulting in calcium signatures that regulate the synthesis of proteins of defense system. These calcium signatures induct different calcium dependent proteins such as calmodulins (CaMs), calcineurin B-like proteins (CBLs), calcium-dependent protein kinases (CDPKs) and other signalling molecules to orchestrate the complex defense signalling. Using advanced biotechnological tools, the role of Ca2+ signalling during plant-microbe interactions and the role of CaM/CMLs and CDPKs in plant defense mechanism has been revealed to some extent. The Emerging perspectives on calcium signalling in plant-microbe interactions suggest that this complex interplay could be harnessed to improve plant resistance against pathogenic microbes. We present here an overview of current understanding in calcium signatures during plant-microbe interaction so as to imbibe a future direction of research.